ROUND TABLE-BASED LEARNING MODELS IN MATHEMATIC LEARNING - Dwi Lestari, Farista; Faelasofi, Rahma; Istiani, Ana (Universitas Muhammadiyah Metro, 2024)
This study aims to find out how the average learning outcome of the pupil is achieved using the round table learning model, together with testing the hypothesis of whether there is a difference between the average pupil learning outcomes of the round table learning model and the conventional learning model. This research is quantitative. The population in this study is the entire pupils of class VIII MTs Nurul Huda Pringsewu. The study sample is pupils from class VIII.1 as the experimental class and class VIII.2 as the control class. The data analysis used is a t-test with the data requirements tested having met the normality and homogeneity test assumptions. Furthermore, the results of this study showed that the achievement of average learning outcomes of students using the round table learning model was 73.66 higher compared to the average study outcome of participants using the conventional learning model which reached 53.5. Then the results of the hypothesis test with the two-party test showed that there was a difference in the average learning outcome on the round table learning model with the conventional learning model.